THE EFFECTIVENESS OF GUIDED DISCOVERY METHOD APPLICATION TOWARD CREATIVE THINKING SKILL AT THE TENTH GRADE STUDENTS OF SMA N 1 TERAS BOYOLALI IN THE ACADEMIC YEAR 2011/2012 - Dwi Saputro, Taufik Widhiyantoro; Indrowati, Meti; Probosari, Riezky Maya (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The purpose of this study was determine the effectiveness of Guided Discovery method application toward creative thinking skill of the tenth grade students of SMA N 1 Teras Boyolali In The Academic Year 2011/2012. This study was a quasi-experimental study using Posttest Only Control Design as a research design. The population in this study was the students of tenth grade in the second semester of SMA N 1 Teras Boyolali in the Academic Year 2011/2012. The sampling technique used Cluster Random Sampling. The collecting data were by test and non test. The datas were analysed by t-test. The result of the research showed that the Guided Discovery application method has an effect on students' science process skill. The highest aspect average of creative thinking skill in the experiment class was obtained in elaboration aspect that is 88.05%, while the lowest in fluency aspect is 83.2%. Based on the sequence of the aspects of creative thinking skill from the highest to the lowest. In details, the creative thinking skill was measured by elaboration : 88.05%, flexibility : 86.56%, originality : 86.56%, fluency : 83.25%. Whereas in the control class, the sequence from the highest to the lowest is flexibility : 74.25%, elaboration : 71.64%, fluency : 70.9%, originality : 69.4%. The conclusion of this research was Guided Discovery learning method was had significantly affecting the creative thinking skill on X grade of SMA Negeri 1 Teras Boyolali. Keywords: Guided Discovery, Creative Thinking Skill